Association between pain sensitivity and gray matter properties in the sensorimotor network in women with irritable bowel syndrome. Issue 4 (10th November 2020) - Grinsvall, Cecilia; Ryu, Hyo Jin; Van Oudenhove, Lukas; Labus, Jennifer S.; Gupta, Arpana; Ljungberg, Maria; Törnblom, Hans; Mayer, Emeran A.; Simrén, Magnus
Abstract: Background: Enhanced perception of visceral stimuli is an important feature of Irritable Bowel Syndrome (IBS), but it is not known whether visceral sensitivity is associated with regional structural brain properties in IBS. Methods: Structural brain magnetic resonance imaging data from 216 women with IBS and 138 healthy women were parcellated with FreeSurfer to define regional gray matter morphometry (volume, cortical thickness, surface area and mean curvature) in the sensorimotor network. General linear models were used to detect group differences between IBS and health. In a second set of 48 female IBS patients, pain threshold, pain intensity ratings during rectal balloon distension, and reported levels of abdominal pain and bloating were correlated with brain regions that showed differences between IBS and health in the first data set. Key Results: Several statistically significant differences between IBS patients and healthy controls were found, mainly higher gray matter volume and cortical thickness in primary somatosensory cortex, secondary somatosensory cortex, and subcortical regions, and lesser gray matter volume, surface area and cortical thickness in posterior insula and superior frontal gyrus. Pain intensity ratings during rectal distension were associated with left primary somatosensory cortical thickness, and pain threshold was associated with right nucleus accumbens volume. Conclusions and Inferences: Regional gray matter differences in sensorimotor network are associated with visceral sensitivity and may represent neuroplastic changes in female IBS patients. Abstract : Regional gray matter differences in sensorimotor network were identified between female IBS patients and female healthy controls. Some regions were associated with visceral sensitivity in IBS and may represent neuroplastic changes in female IBS patients.